2013
DOI: 10.3892/ijo.2013.2105
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of infection with human papillomavirus: The role of the p53 tumor suppressor protein and E6/E7 zinc finger proteins

Abstract: Human papillomaviruses (HPV) are small circular, double-stranded DNA viruses infecting epithelial tissues. HPV types can be classified both as high-risk or low-risk. Of the more than 120 different identified types of HPV, the majority are involved in infections of the genital tract, cancer of the cervix, vulva, vagina and penis, and of non-anogenital localizations, such as the head and neck areas. From the point of view of the infection, human papillomaviruses have developed several molecular mechanisms to ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 101 publications
(110 reference statements)
1
45
0
3
Order By: Relevance
“…The multifunctional activities of HR-HPV E6 and E7 oncoproteins have been subject to extensive research throughout the past decades, and it has been suggested that some of these activities may act in favor of HPV persistence; examples of E6/E7 oncoprotein functions that may promote HPV persistence are: modulation of cell-cycle regulators to maintain long-term replication (27)(28)(29), repression of the function of immune system (15,30,31), degradation of p53 tumor-suppressor protein (16,32), telomerase activation (33) and enhanced genomic instability, which could result in stabilization of the viral genome by genomic integration. Although it remains subject to further elucidation if and how these activities contribute to HPV persistence, it is of clinical relevance to establish the association between HPV persistence and presence of elevated expression of the E6 oncoprotein of HPV types 16 and 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multifunctional activities of HR-HPV E6 and E7 oncoproteins have been subject to extensive research throughout the past decades, and it has been suggested that some of these activities may act in favor of HPV persistence; examples of E6/E7 oncoprotein functions that may promote HPV persistence are: modulation of cell-cycle regulators to maintain long-term replication (27)(28)(29), repression of the function of immune system (15,30,31), degradation of p53 tumor-suppressor protein (16,32), telomerase activation (33) and enhanced genomic instability, which could result in stabilization of the viral genome by genomic integration. Although it remains subject to further elucidation if and how these activities contribute to HPV persistence, it is of clinical relevance to establish the association between HPV persistence and presence of elevated expression of the E6 oncoprotein of HPV types 16 and 18.…”
Section: Discussionmentioning
confidence: 99%
“…Although expressed at minute levels in most HPV infections, certain molecular events (for example loss or mutation of the viral E2 gene product) can result in elevated expression of E6 and E7 oncoproteins. Both E6 and E7 are multifunctional oncoproteins that interfere with numerous cellular pathways and altogether drive cellular transformation (16). Chiefly, the E6 oncoprotein acts antiapoptotic, for example, by driving p53 tumor suppressor into the ubiquitin-dependent degradation pathway, whereas the E7 oncoprotein promotes proliferation, for example, by inactivating pRB (15,17).…”
Section: Introductionmentioning
confidence: 99%
“…These specific viral genes express oncoproteins (such as E6 and E7 proteins) that can be inserted into the host's cell genome (6). Therefore, E6 and E7 proteins may be critical for identifying HR HPV, and consequently could be a potential new biomarker for CC diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous reports from the International Agency for Research on Cancer, HPV could be classified into high-risk (HR) types (16,18,31,33,35,39,45, 51, 52, 56, 58, 59, 68, 73 and 82), probable HR types (26,53 and 66) and low-risk types (6,11,40,42,43,44,54,61,70,72, 81 and CP6108) (3).…”
Section: Introductionmentioning
confidence: 99%
“…Е7 связывается с протеинфосфатазой, что приводит к то-му, что сигнал не блокируется, а передается дальше. В ре-зультате клетка не подвергается апоптозу и сохраняет свою жизнеспособность [8,9].…”
unclassified